Secularization and Tradition In Four Arab Countries: A Comparative Content Analysis of Reading Textbooks (American Journal of Islam and Society, 1986)
I. IntroductionThe educational process is a combination of three important elements:teacher, student, and communication. This study focused on the third elementin examining second grade reading textbooks in four Arab countries:Jordan, Libya, Saudi Arabia, and Syria. Textbooks are not the only importantelement in the communication dimension nor do texts provide the onlymessage students learn or the only influence in the educational process. Textbookshave the advantage, however, of being subject to content analysis andrepresent symbolic interaction as an effective means to translate the culturalheritage of any nation.Each country has its own books, and has its own methods to educateyoungsters consistent with broad goals and national needs. Religious educationin many Middle Eastern countries is a gradual and continuing processwhich begins early in the educational life of the individual. Such educationis complete, comprehensive, and is intended even at the elementary level todevelop understanding of religious and social behavior.Most of the content of books in Arab countries is prepared to reflect theseparated worlds of males and females, displaying the supreme societal,religious, psychological, and physical power of men over women. Educationalleaders and decision makers, at least in the Middle East, seem to be effectiveadvocates of traditional values and are concerned with the positive impactof the educational process. The primary aims of the educational system in ...